Modelos de regressão linear heteroscedásticos com erros t-Student: uma abordagem bayesiana objetiva - Souza, Aline Campos Reis de (Universidade Federal de São Carlos, 2016)
In this work , we present an extension of the objective bayesian analysis made in Fonseca et al. (2008), based on Je reys priors for linear regression models with Student t errors, for which we consider the heteroscedasticity assumption. We show that the posterior distribution generated by the proposed Je reys prior, is proper. Through simulation study , we analyzed the frequentist properties of the bayesian estimators obtained. Then we tested the robustness of the model through disturbances in the response variable by comparing its performance with those obtained under another prior distributions proposed in the literature. Finally, a real data set is used to analyze the performance of the proposed model . We detected possible in uential points through the Kullback -Leibler divergence measure, and used the selection model criterias EAIC, EBIC, DIC and LPML in order to compare the models.
Heteroscedastics linear regression models with Student-t errors: an objective bayesian analysis
Keywords: Distribuição a priori de Je reys; Inferência robusta; Erros t-Student; Modelos de regressão linear heteroscedásticos; Je reys prior; Robust inference; Student t errors; Heteroscedastic linear regression models; CIENCIAS EXATAS E DA TERRA